Induction of steatosis in primary human hepatocytes recapitulates key pathophysiological aspects of metabolic dysfunction-associated steatotic liver disease: MASLD and alcohol-related liver diseases - Kwon, Yun; Gottmann, Pascal; Wang, Surui; Tissink, Joel; Motzler, Karsten; Sekar, Revathi; Albrecht, Wiebke; Cadenas, Cristina; Hengstler, Jan G.; Schürmann, Annette; Zeigerer, Anja (Journal of hepatology, 2025)
Background & Aims - Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common cause of chronic liver disease. Owing to limited available treatment options, novel pre-clinical models for target selection and drug validation are warranted. We have established and extensively characterized a primary human steatotic hepatocyte in vitro model system that could guide the development of treatment strategies for MASLD. - Methods - Cryopreserved primary human hepatocytes from five donors varying in sex and ethnicity were cultured with free fatty acids in a 3D collagen sandwich for 7 days and the development of MASLD was followed by assessing classical hepatocellular functions. As proof of concept, the effects of the drug firsocostat (GS-0976) on in vitro MASLD phenotypes were evaluated. - Results - Incubation with free fatty acids induced steatosis, insulin resistance, mitochondrial dysfunction, inflammation, and alterations in prominent human gene signatures similar to patients with MASLD, indicating the recapitulation of human MASLD in this system. The application of firsocostat rescued clinically observed fatty liver disease pathologies, highlighting the ability of the in vitro system to test the efficacy and potentially characterize the mode of action of drug candidates. - Conclusions - Altogether, our human MASLD in vitro model system could guide the development and validation of novel targets and drugs for the treatment of MASLD. - Impact and implications - Due to low drug efficacy and high toxicity, clinical treatment options for metabolic dysfunction-associated steatotic liver disease (MASLD) are currently limited. To facilitate earlier stop-go decisions in drug development, we have established a primary human steatotic hepatocyte in vitro model. As the model recapitulates clinically relevant MASLD characteristics at high phenotypic resolution, it can serve as a pre-screening platform and guide target identification and validation in MASLD therapy.
Online verfügbar: 6. Juli 2024, Artikelversion: 16. Dezember 2024
Gesehen am 06.05.2025